Issues and Challenges in the Detection of Suspected Tuberculosis Cases in Rawasari Public Health Center, Jambi City - Aglen, Siti Setya Sari; Nuriyah; Haqquefitria, Rati Nurul (Scientific Of Environmental Health and Diseases, 2025)
Background: Based on WHO data, Indonesia occupies the second highest position in the world  for TB burden. Finding TB cases is the first step in TB control activities. Finding and curing infectious  TB patients can significantly reduce morbidity and mortality due to TB. The high rate of TB case  discovery is related to the achievement of TB suspect discovery. The higher the  achievement of finding TB suspects, it is hoped that the greater number of positive TB cases found will be. Method: This study uses a descriptive method with primary and secondary data collection at the  Rawasari Health Center, Jambi City. The data was processed manually and analyzed the content  with the selected problem solving brainstorming method, then an activity pro posal plan and monitoring and evaluation were carried out. Result: The discovery of TB suspect cases by Rawasari Health Center from Januari to December  2024, with a target of 1.015 people, reached only 255 people (25.1%) and the discovery TB cases with target of 209 people reached only 42 people (20.09%). Of the 40 patient respondents who  visited the Rawasari Community Health Center, Jambi City in December 2024, 27 people (67.5%)  had a good level of knowledge and 31 people (77.5%) had a good level of attitude. Conclusion: In this study, it was found that the priority problem was the lack of discovery of TB cases with the most dominant cause being TB screening is still lacking by officers from various clusters.